2022
DOI: 10.1007/s10924-022-02556-5
|View full text |Cite
|
Sign up to set email alerts
|

Epoxidation of Tall Oil Fatty Acids and Tall Oil Fatty Acids Methyl Esters Using the SpinChem® Rotating Bed Reactor

Abstract: Tall oil fatty acids are a second-generation bio-based feedstock finding application in the synthesis of polyurethane materials. The study reported tall oil fatty acids and their methyl esters epoxidation in a rotating packed bed reactor. The chemical structure of the synthesized epoxidized tall oil fatty acids and epoxidized tall oil fatty acids methyl ester were studied by Fourier-transform infrared spectroscopy. Average molecular weight and dispersity were determined from gel permeation chromatography data.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 29 publications
(42 reference statements)
0
1
0
Order By: Relevance
“…The bio-based polyurethane market share in 2023 was only 8.98% [ 29 ]. It has been shown that only one of the rigid PU foam components can feasibly be produced economically from bio-based feedstocks – bio-based polyols [ 30 , 31 , 32 , 33 ]. The other component—polyisocyanate—is a petrochemical product, and it is unlikely that it will be produced in a sustainable manner [ 34 , 35 , 36 ].…”
Section: Introductionmentioning
confidence: 99%
“…The bio-based polyurethane market share in 2023 was only 8.98% [ 29 ]. It has been shown that only one of the rigid PU foam components can feasibly be produced economically from bio-based feedstocks – bio-based polyols [ 30 , 31 , 32 , 33 ]. The other component—polyisocyanate—is a petrochemical product, and it is unlikely that it will be produced in a sustainable manner [ 34 , 35 , 36 ].…”
Section: Introductionmentioning
confidence: 99%